A systematic review of the impact of psychosocial factors on immunity: Implications for enhancing BCG response against tuberculosis. (April 2020) - Hayward, Sally E.; Dowd, Jennifer B.; Fletcher, Helen; Nellums, Laura B.; Wurie, Fatima; Boccia, Delia
Abstract: Background: Tuberculosis (TB) remains an urgent global public health priority, causing 1.5 million deaths worldwide in 2018. There is evidence that psychosocial factors modulate immune function; however, how this may influence TB risk or BCG vaccine response, and whether this pathway can be modified through social protection, has not been investigated. This paper aims to: a) systematically review evidence of how psychosocial factors influence the expression of biomarkers of immunity, and b) apply this general evidence to propose plausible TB-specific pathways for future study. Methods: Papers reporting on the impact of psychosocial stressors on immune biomarkers in relation to infectious disease risk were identified through a search of the databases MEDLINE, PsycINFO, Global Health and PsycEXTRA alongside reference list and citation searching of key papers. Data extraction and critical appraisal were carried out using a standardised form. The findings were tabulated and synthesised narratively by infectious disease category, and used to propose plausible mechanisms for how psychosocial exposures might influence immune outcomes relevant to TB and BCG response. Results: 27, 026 citations were identified, of which 51 met the inclusion criteria. The literature provides evidence of a relationship between psychosocial factors and immune biomarkers. While the direction and strength of associations is heterogenous, some overarching patterns emerged: adverse psychosocial factors (e.g. stress) were generally associated with compromised vaccine response and higher antibody titres to herpesviruses, and vice versa for positive psychosocial factors (e.g. social support). Conclusions: The evidence identifies pathways linking psychosocial factors and immune response: co-viral infection and immune suppression, both of which are potentially relevant to TB and BCG response. However, the heterogeneity in the strength and nature of the impact of psychosocial factors on immune function, and lack of research on the implications of this relationship for TB, underscore the need for TB-specific research. Highlights: It is unknown whether and how psychosocial factors could modulate immunity to TB. We systematically review studies of psychosocial influences on immune function. There is evidence for an association between psychosocial factors and immunity. The nature and strength of associations are heterogeneous. Further research is required to establish TB-specific pathways.